PEMBERIAN TEPUNG Spirulina platensis PADA PAKANTERHADAP KECERAHAN WARNA IKAN BADUT(Amphiprionocellaris) - Hadijah; Muhammad Junaidi; Dewi Putri Lestari (Universitas Mataram, 2020)
This study aims to determine the exact dosage of S. platensis flour in feed to improve the color quality of clown fish. The method used was an experimental method using a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications, P0 (control), P1 (S. platensis meal 1%), P2 (S. platensis meal 3%), P3 (S. platensis meal 5%), and P4 (S. platensis meal 7%). The results showed that there was no significant effect on the level of color brightness and survival rate, but had a significant effect on the growth of absolute weight, absolute length growth, specific weight growth rate, and specific length growth rate. It is known that P2 (S. platensis meal 3%) is the highest treatment at the level of color brightness (181.6%), absolute weight growth with 0.26 g and the best treatment at a specific weight growth rate with 1.44 g. Whereas P4 (S. platensis meal 7%) is the best treatment at absolute length growth with 0.62 cm and the best treatment at the specific length growth rate with 0.73 cm. Based on the results of the study, it was concluded that the addition of Spirulina platensis meal to feed at a dose of 3% (Treatment 2) is the doses to increase the brightness of the clown fish.